1999
DOI: 10.1002/(sici)1099-1166(199910)14:10<866::aid-gps38>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental symptoms in Parkinson's disease are important contributors to caregiver distress

Abstract: Objective To determine the emotional and social distress of caring for a patient with Parkinson's disease and to explore the impact of motor and mental symptoms in subjects with Parkinson's disease on their caregivers' situation. Design Cross‐sectional, population‐based study using self‐report questionnaires to measure caregiver distress and rating scales to assess patient symptomatology. Setting Neurology and old age psychiatry services in Stavanger, Norway. Subjects Caregivers of 94 home‐dwelling patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
126
1
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 426 publications
(136 citation statements)
references
References 21 publications
3
126
1
6
Order By: Relevance
“…Among those patients who exhibited the symptom, higher (apathy and aberrant motor behavior) or equal severity was found in PDD than AD patients. Recent studies have demonstrated that the psychiatric symptoms in PD are important for the quality of life for the patients themselves (Karlsen et al, 1999) and their caregivers (Aarsland et al, 1999b), as well as for the need for long term nursing home care (Aarsland et al, 2000). Accordingly, given the high risk for developing dementia in PD, our ®ndings underscore the clinical importance of neuropsychiatric symptoms in this patient group.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Among those patients who exhibited the symptom, higher (apathy and aberrant motor behavior) or equal severity was found in PDD than AD patients. Recent studies have demonstrated that the psychiatric symptoms in PD are important for the quality of life for the patients themselves (Karlsen et al, 1999) and their caregivers (Aarsland et al, 1999b), as well as for the need for long term nursing home care (Aarsland et al, 2000). Accordingly, given the high risk for developing dementia in PD, our ®ndings underscore the clinical importance of neuropsychiatric symptoms in this patient group.…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies have reported that neuropsychiatric symptoms are common in PD, particularly in those with dementia (Aarsland et al, 1999a), and that these symptoms have important clinical consequences for the quality of life of PD patients (Karlsen et al, 1999) and caregivers (Aarsland et al, 1999b). Although the relationship between neuropsychiatric symptoms and neuropathology is far from straightforward, such symptoms may provide information regarding which brain structures are involved in PDD.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a very recent study, Woods and Tröster [6] reported that a prodromal frontal/executive dysfunction whose characteristics are rather comparable to what we observed, can predict the incidence of dementia in PD. As underlined by these authors, dementia in PD is associated, among others with an increase in caregiver distress and the social burden [1,2], and an early identification of incident dementia may help to set up an appropriate medical and psychosocial management of this disorder. Furthermore, the idea that treatments such as acetylcholinesterase inhibitors can slow down cognitive and behavioural disorders in demented patients [13,19,45] also represents an important challenge since an early administration seems to increase their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Current pharmacological and surgical treatments are able to moderate symptoms in many PD patients for relatively long periods of time and prolong the time of necessary care provision. The majority of PD patients live in the community, and relatives, primarily partners, provide much of the long-term care of the patients [1]. Caring for a family member with PD is a long, stressful process which imposes heavy demands on emotional, physical and financial resources and thus influences quality of life [3,5,7,22,25,30,31,34].…”
Section: Introductionmentioning
confidence: 99%